Effect of Parental Corporal Punishment on Endorsement of Its Use: Moderated Mediation by Parent Gender and Attitudes Toward Corporal Punishment - Walker, Courtney S. (Journal of interpersonal violence, 2021)
Previous research has examined the factors that place an individual at a risk of using harsh discipline on children. Chief among these predictors is an individual’s own experience of corporal punishment, as well as favorable attitudes toward corporal punishment as a parenting strategy. However, few studies have examined the relationships among these variables in emerging adults. Thus, the current study advanced this area of research by examining how attitudes toward corporal punishment mediated the association between the experience of corporal punishment within the past year and the endorsement of corporal punishment as a future parenting strategy of choice among emerging adults when presented with a vignette. In addition, the current study examined gender differences among study variables, including participants’ parental disciplinary practices and whether participants were more accepting of using corporal punishment against a boy or girl in a hypothetical vignette. Participants (N = 393; Mage = 19.21) completed an online survey that included a hypothetical vignette depicting child misbehavior. Results from the current study suggested the experience of corporal punishment from mothers appeared to have more of an influence on the decision to endorse corporal punishment in the vignette for both emerging adult males and females. The findings from the current study highlight the importance of reducing the use of corporal punishment as a discipline strategy, as the experience of corporal punishment appears to shape attitudes which may favor future use of the practice.